Identification of Cation Reaction and Separation of Group I Cations - Olena Silvia; Olivia Ghina Olia; Rahma Dika Aulia Nasution; Rani Sakila Nasution; Silvia Deswinta Maharani Damanik (Indonesian Journal of Chemical Connections, 2023)
This study focuses on the identification of cation reactions and the separation process of Group I cations in qualitative analysis. The research examines the characteristic reactions of silver, lead, and mercury(I) cations using various reagents. Both dry and wet reaction methods are employed to distinguish and separate these cations from solution mixtures. The results provide a systematic approach for Group I cation identification in laboratory practice.